Leaf traits divergence and correlations of woody plants among the three plant functional types on the eastern Qinghai-Tibetan Plateau, China - Xing, Hongshuang; Shi, Zuomin; Liu, Shun; Chen, Miao; Xu, Gexi; Cao, Xiangwen; Zhang, Miaomiao; Chen, Jian; Li, Feifan (Frontiers in Plant Science, 2023)
Leaf traits are frequently used to describe the life history of plants. They may vary according to plant functional type (PFT), the covariant patterns of leaf traits and the effects of environmental changes to plants. Our study took the common woody plants as the research object on the eastern Qinghai-Tibetan Plateau, and 771 leaf samples of woody plants (containing 110 species) were collected from 50 sites. They were divided into 3 PFTs based on leaf habit and form, being classified as either needle-leaved evergreens (NE), broad-leaved evergreens (BE) and broad-leaved deciduous (BD). We investigated the variation of leaf traits of woody plants in this region. The differences in key leaf traits covariation were evaluated among NE, BE and BD. The response and adaptive strategies of leaves from different PFTs to the environment were discussed, and various factors of leaf traits variation were analyzed. There were significant differences in leaf traits of different PFTs. They were all shown NE>BE>BD that LT, LDMC, LMA, C/N, and Nmass except for Narea. There were differences in the coordination of multiple traits. Leaf traits were susceptible to environmental factors such as elevation and MAT (mean annual temperature), water was not the main factor of leaf traits variation in this region. Different PFTs showed discrepant survival strategies. We found that NE showed conservative survival strategy, while BD showed acquisitive survival strategy, and BE was somewhere in between. Comprehensive analysis indicated that temperature was an important environmental factor affecting the leaf traits variation of woody plants, and leaf traits of 3 PFTs had different responses to environmental changes. This work explained the variation of leaf traits on a regional scale and indicated the relationship of leaf traits - PFT - environment. These findings have better significance for the development of regional scale dynamic vegetation models and the study of plant response and adaptation to environmental changes.